Does Having a Female Sarpanch Promote Service Delivery for Women and Democratic Participation of Women? Evidence from Maharashtra, India - Dhanmanjiri Sathe; Stephan Klasen; Jan Priebe; Mithila Biniwale (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2013)
In this paper we examine the impact of mandated reservations for female sarpanchs in the gram panchayats on perceptions of service delivery and women's democratic participation. Using survey data from the Sangli district, Maharashtra, we find that the availability of basic, public services is significantly higher in female sarpanch villages as compared to the male sarpanch villages, when the elections have been held three to 3 1/2 years before the survey; while service delivery in villages with more recently elected female sarpanchs is worse. Further, the reservations have a significant, positive impact on the democratic participation of the women in the female sarpanch villages, again driven by the impact of female sarpanchs elected 3 years before the survey. The democratic participation of women, in turn, affects the availability of services very robustly. The findings suggest that the positive effects in terms of service delivery and democratic participation will take some time to materialize.
Keywords: 330; Mandated reservations; Service delivery; political participation